Observation of Conventional Therapy Combined with PNF Technology to Treat Elbow Joint Dysfunction after Trauma Surgery - Shaoyun SHI; Huiping LU; Guobiao YE; San LI; Jie Liang (康复学报)
Objective:To study the effect of regular strength training, joint mobilization combined with proprioceptive neuromuscular facilitation (PNF) technology on postoperative dysfunction of elbow joint due to common trauma.Methods:According to random draw method, one hundred patients with postoperative dysfunction of traumatic elbow joint were randomly divided into the routine group and the experimental group with 50 cases in each group. They included 40 cases of elbow joint fractures and dislocations, 10 cases of capitulum humerus fractures, 10 cases of trochlea humeri fractures, 10 cases of capitulum radius fractures, 10 cases of olecroanon fractures, 10 cases of intercondylar humerus fractures, 10 cases of lower end of the humerus fractures. Patients of the routine group received joint mobilization, muscle strength training, joint motion technique, physical therapy and other systematic training, while patients of the experimental group received PNF technology treatment besides. Pre-treatment and 8 weeks after the treatment, evaluations of hospital for special surgery scoring system (HHS) elbow score were carried out in both groups, including pain, function, sagittal joint range of motion, muscle strength, flex contracture, extend contracture, pronation, supination, total score, assessment, etc.Results:Before rehabilitation, there was no obvious difference of each assessment index score of average and total between the routine and experimental group (P>0.05). Total scores of both groups belonged to poor domain. After 8 weeks treatment, evaluations of HHS elbow score of both groups were improved significantly (P<0.05), including pain, function, joint range of motion, muscle strength, contracture, total score, etc. Compared with the routine group (total score 76.70±7.22, assesment medium), except for pain improvement being without apparent difference, indexes of the experimental group (total score 81.96±6.79, assesment fine) were improved more significantly (P<0.05).Conclusion:Conventional therapy combined with PNF technology to treat postoperative dysfunction of traumatic elbow joint are more effective, deserving for clinical generalization.